Genetic Lineage Distribution Modeling to Predict Epidemics of a Conifer Disease - Herpin-Saunier, Naomie Y. H.; Sambaraju, Kishan R.; Yin, Xue; Feau, Nicolas; Zeglen, Stefan; Ritokova, Gabriela; Omdal, Daniel; Côté, Chantal; Hamelin, Richard C. (Frontiers in Forests and Global Change, 2022)
A growing body of evidence suggests that climate change is altering the epidemiology of many forest diseases. Nothophaeocryptopus gaeumannii (Rhode) Petrak, an ascomycete native to the Pacific Northwest and the causal agent of the Swiss needle cast (SNC) disease of Douglas-fir [Pseudotsuga menziesii (Mirbel) Franco], is no exception. In the past few decades, changing climatic conditions have coincided with periodic epidemics of SNC in coastal forests and plantations from Southwestern British Columbia (B.C.) to Southwestern Oregon, wherein an increase in the colonization of needles by N. gaeumanii causes carbon starvation, premature needle shedding and a decline in growth. Two major sympatric genetic lineages of N. gaeumannii have been identified in the coastal Pacific Northwest. Past research on these lineages suggests they have different environmental tolerance ranges and may be responsible for some variability in disease severity. In this study, we examined the complex dynamics between biologically pertinent short- and long-term climatic and environmental factors, phylogenetic lineages of N. gaeumannii and the severity patterns of the SNC disease. Firstly, using an ensemble species distribution modeling approach using genetic lineage presences as model inputs, we predicted the probability of occurrence of each lineage throughout the native range of Douglas-fir in the present as well as in 2050 under the “business as usual” (RCP8.5) emissions scenario. Subsequently, we combined these model outputs with short-term climatic and topographic variables and colonization index measurements from monitoring networks across the SNC epidemic area to infer the impacts of climate change on the SNC epidemic. Our results suggest that the current environmental tolerance range of lineage 1 exceeds that of lineage 2, and we expect lineage 1 to expand inland in Washington and Oregon, while we expect lineage 2 will remain relatively constrained to its current range with some slight increases in suitability, particularly in coastal Washington and Oregon. We also found that disease colonization index is associated with the climatic suitability of lineage 1, and that the suitability of the different lineages could impact the vertical patterns of colonization within the crown. We conclude that unabated climate change could cause the SNC epidemic to intensify.